Primary prevention of cardiovascular disease: focus on improving behavioral risk factors - V. S. Chulkov; E. S. Gavrilova; Vl. S. Chulkov; E. D. Pankova; E. A. Lenets; P. E. Tkachenko (Российский кардиологический журнал, 2021)
Public health strategies for the detection, prevention and treatment of cardiovascular diseases (CVDs) can be implemented at many levels as follows: from individual behavioral alterations to population-based strategies that affect different national and cultural communities. Despite the fact that the priority of primary prevention is treating hypertension and hyperlipidemia, great importance is given to improving behavioral and biological risk factors. Dietary modification, exercise and smoking cessation are specific interventions that can be targeted to reduce CVD risk at both the individual and population levels. Following a healthy lifestyle can potentially change factors such as overweight/obesity, hyperlipidemia, type 2 diabetes, and hypertension. The aim of this review was to present and summarize new data on the primary cardiovascular prevention with a focus on improving behavioral risk factors considered in the current guidelines.